2016
DOI: 10.1596/1813-9450-7690
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interventions in Tax Compliance: Evidence from Guatemala

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 37 publications
(38 reference statements)
5
79
1
8
Order By: Relevance
“…For rms covered by third-party information, the eects of emails that listed specic examples of information known to the tax authority were generally higher. All treatment eects estimated here equal or exceed those from other communication experiments (Castro and Scartascini 2015;Del Carpio 2014;Fellner, Sausgruber, and Traxler 2013;Kettle et al 2016), which suggests that combining dierent messages contents that have proved to be impactful individually (deterrence, 27 Note that we consider payments made by the taxpayer with her annual declaration, and ignore the quarterly advance payments during the year. If a taxpayer is a non-ler and also has outstanding advance payments, those would have to be made with the annual declaration, and are thus considered in our estimation.…”
Section: Income Tax Compliancementioning
confidence: 64%
See 2 more Smart Citations
“…For rms covered by third-party information, the eects of emails that listed specic examples of information known to the tax authority were generally higher. All treatment eects estimated here equal or exceed those from other communication experiments (Castro and Scartascini 2015;Del Carpio 2014;Fellner, Sausgruber, and Traxler 2013;Kettle et al 2016), which suggests that combining dierent messages contents that have proved to be impactful individually (deterrence, 27 Note that we consider payments made by the taxpayer with her annual declaration, and ignore the quarterly advance payments during the year. If a taxpayer is a non-ler and also has outstanding advance payments, those would have to be made with the annual declaration, and are thus considered in our estimation.…”
Section: Income Tax Compliancementioning
confidence: 64%
“…As expected, the observed treatment eect of our emails is substantially larger than treatment eects in most other studies. Besides, our study is one of few in this literature to focus on rms, including corporations, as opposed to individual taxpayers, and the rst with Kettle et al (2016) to focus on tax ling. 11 Indeed, most studies in this literature have focused on correct reporting of liabilities or on the payment of already assessed liabilities, such as property tax liabilities.…”
Section: Policy Research Working Paper 7850mentioning
confidence: 99%
See 1 more Smart Citation
“…Field experiments encouraging honest tax reporting, in particular, have a long tradition among economists, psychologists and policy scholars [8,9,10,11,12]. Some have found that the mention of increased audits or penalties has a positive impact on tax compliance, e.g., [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Natural logarithm of reported items in the income tax return, namely Sales, previous studies (for instance in the work of Kettle, Hernandez, Ruda, and Sanders, 2016). This outcome variable will be estimated by Probit estimation.…”
Section: Methodsmentioning
confidence: 99%